Forgiveness in Muslim Indonesia: A Cross-Sectional Study of Emotional Intelligence and Social Integration during Halal Bihalal - Marimbun Marimbun; Azizah Abdullah; Rizky Andana Pohan; Nengsih Nengsih; Sabrida M Ilyas; Wan Chalidaziah (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
Forgiveness is a vital component of interpersonal harmony and community resilience, particularly within religious and cultural contexts. In Indonesia, the halal bihalal tradition, an Islamic communal ritual of mutual forgiveness following Eid al-Fitr, represents a unique socio-religious practice of reconciliation. This study aims to examine the psychosocial predictors of forgiveness within this ritual context using a quantitative cross-sectional design involving 512 Indonesian Muslim respondents across five provinces. A structured online questionnaire was administered to assess emotional intelligence, social integration, and dispositional forgiveness. Multiple linear regression analysis revealed that emotional intelligence (β = 0.412, p < 0.001) and social integration (β = 0.192, p < 0.001) significantly predicted forgiveness, accounting for 39.1% of its variance. The findings affirm that forgiveness is a socially embedded and emotionally regulated process, reinforced by spiritual rituals, particularly during Ramadan and post-Eid gatherings. This study extends forgiveness theories by incorporating collectivist, spiritual, and ritualized dimensions, highlighting the role of halal bihalal as a culturally grounded mechanism for emotional repair and social cohesion. Limitations include the regional scope and reliance on self-report measures. Future research is recommended to explore forgiveness as a ritualized practice across diverse religious and ethnic contexts. Keywords: halal bihalal ritual, emotional intelligence, social integration, forgiveness, emotional well-being, religious-based psychoeducation